Meningkatkan Hasil Belajar Ipa Pada Materi Peristiwa Dalam Kehidupan Melalui Penerapan Model Pembelajaran Berbasis Masalah (Pbm) Di Kelas V Sdn 16 Kabawo - Erniwati Erniwati; La Sisi; Arna Juwairiyah (Jurnal Sultra Elementary School, 2021)
The results of this study showed that the implementation of the Problem-Based Learning (PBL) model could improve students’ learning outcomes. In the first cycle, the average score obtained by students was 69.44, which increased in the second cycle to 74.44. The percentage of student mastery in the first cycle was only 73.33%, with 11 out of 15 students achieving mastery, and it increased to 86.67% in the second cycle, with 13 out of 15 students meeting the mastery criteria. These findings indicate that the use of the Problem-Based Learning model is effective in enhancing students’ learning outcomes.